Safety and efficacy of Beltherm MP/ML (endo‐1, 4‐beta‐xylanase) as a feed additive for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding, turkeys for breeding purposes and minor poultry species. (1st March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Beltherm MP/ML contains endo‐1, 4‐beta‐xylanase and is intended to be used as a zootechnical additive for poultry species. The safety and efficacy of the additive have been evaluated by the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) in 2017. In that assessment, the additive and the production strain, a genetically modified strain of Bacillus subtilis, were characterised in full. No viable cells of the production strain were detected in the final additive, but recombinant DNA from the production strain was detected. Considering that the production strain does not carry genetic sequences of concern, the presence of DNA was considered per se of no safety concern by the Panel. The safety of the additive for the target species, consumers and environment was established, but the Panel concluded that the additive should be considered as a respiratory sensitiser. Regarding the efficacy, it was concluded that the additive has a potential to be efficacious in chickens for fattening and extended/extrapolated the conclusion to chickens reared for laying and minor poultry species for fattening. However, the Panel could not conclude on the efficacy of the additive in turkeys for fattening, reared for breeding or for breeding purposes. The Panel concluded, based on the new guidance on the efficacy for feed additives, that the conclusion on the efficacy in chickens for fattening can be extrapolated to turkeys for fattening/reared for breeding purposes. New data in turkeys for fattening would support the extrapolation. No data has been provided to support the efficacy in turkeys for breeding purposes and therefore no conclusion could be drawn. Finally, the applicant has proposed, in the current submission, a modification of the manufacturing process to remove the presence of DNA from the production strain in the final product, the removal was confirmed by analyses.